Kecerdasan Utama Muhammad SAW dan Relevansinya dengan Ilmu Kecerdasan Modern - Rohana Rohana; Donant Alananto Iskandar (LPMP Imperium, 2021)
This study shows the primacy of the intelligence of the Prophet Muhammad Rasulullah SAW in terms of intellectual, emotional, and spiritual intelligence. Various narrations have described the intelligence of the Prophet Muhammad, including memory intelligence in remembering or memorizing revelations that were revealed, being kind and respectful towards non-Muslims at that time, so that the Prophet became a figure admired by the world not only for Muslims but also for non-Muslims. The Prophet became the complete character in intelligence because he had the highest intelligence; namely, spiritual intelligence, which he showed through his devotion to Allah, surrendered to Him and looked at things in a deep essence. These narrations prove that the Prophet Muhammad SAW had been prepared by Allah SWT as an Apostle not only for the ignorant Arab society at that time but also for mankind until the end of time. All of this Prophet's intelligence was in accordance with intelligence in psychological studies in general.